Death brings a shadow - Simpson, Rosemary, 1942- (Simpson, Rosemary, 1942- Gilded Age mystery., 2019)
"In spring 1889, Prudence and Geoffrey set sail from New York Harbor on a private yacht bound for Bradford Island, where her friend Eleanor Dickson is to be wed. The Sea Islands along the Georgia coast serve as a winter playground for the likes of the Carnegies, Rockefellers, Vanderbilts, and Dicksons. Despite her Yankee pedigree, Eleanor is marrying a Southern gentleman, Teddy Bennett, and Prudence is thrilled to be the maid of honor. But days before the wedding, the bride is nowhere to be found. A frantic search of the island turns up her drowned corpse in an alligator-infested swamp. Prudence is devastated, but as they prepare the body for burial, she and Geoffrey discover evidence of bruising that indicates Eleanor was held under -- most dishonorably murdered. Determined to seek justice for her beloved friend, Prudence begins to investigate with Geoffrey's help and is quickly led into a morass of voodoo spells and dark deeds from the days of slavery. As Prudence and Geoffrey pursue a killer, they soon discover that Eleanor will not be the last to die on Bradford Island." --